(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
In this paper, I first present Blazhe Koneski’s contribution to the field of translating Slovenian poetry into Macedonian, and then I focus on the translations of his works into Slovenian. Given Koneski’s rich literary opus, the proportion of translations of his poems and prose into Slovene may not be very large, but it includes poems from almost all collections, some translations even appearing simultaneously with or shortly after the publications in the original. After the publication of his selected poetry book in 1977 (Poezija), Slovenian translations of Koneski’s literary works appeared only in newspapers, magazines, scholarly articles, collections, and only on the occasion of the poet’s centenary, again in the form of a book entitled Marko Krale – Kraljevič Marko. In this paper I also present a valuable analysis of the translations (of Slovenian poetry translated into Macedonian by Koneski and of Koneski’s poetry translated into Slovenian by Ivan Minatti and Fran Albreht) by Bistrica Mirkulovska. Keywords: Blazhe Koneski; Macedonian literature; Macedonian-Slovenian literary bonds; intercultural mediation; literary translation.